Influence of Ozone Forcing on 21st Century Southern Hemisphere Surface Westerlies in CMIP6 Models. Issue 6 (18th March 2022) - Revell, L. E.; Robertson, F.; Douglas, H.; Morgenstern, O.; Frame, D.
Abstract: The tropospheric westerly jet is a key feature of Southern Hemisphere climate. In recent decades the jet strengthened in austral summer (December–February [DJF]) and moved poleward owing to the Antarctic ozone hole. Future jet trends will be influenced by recovery of the Antarctic ozone hole and greenhouse gas (GHG) forcing. Here, we examine 21st century projections of ozone, temperature and winds in the sixth Coupled Model Intercomparison Project models with (CHEM) and without (NOCHEM) interactive chemistry. NOCHEM models use an ozone data set that was produced with GHG forcings inconsistent with those used by CHEM models, leading to less ozone recovery in the Antarctic springtime lower stratosphere. This propagates to different stratospheric temperature projections and DJF westerly winds: NOCHEM models project a 78 ± 52% stronger increase in DJF westerly wind speeds than CHEM models under the high GHG emissions scenario SSP585. Our results show the importance of simulating stratospheric ozone accurately for Southern Hemisphere climate change projections. Plain Language Summary: Global climate models must simulate Southern Hemisphere westerly winds accurately to simulate other key features of Southern Hemisphere midlatitude climate. During Southern Hemisphere summer, westerly winds are partly influenced by the Antarctic ozone hole. Global climate models simulate ozone in one of two ways: either they calculate ozone concentrations online via an interactive chemistry scheme, or they prescribe a precomputed ozone data set. The former approach is computationally expensive, yet the latter approach means that ozone cannot respond to internal changes in the model, potentially causing errors. In the sixth Coupled Model Intercomparison Project (CMIP6), most models prescribed ozone rather than calculating it online. Unfortunately, the ozone data set they prescribed is not consistent with other forcings used by the CMIP6 models, therefore models with and without interactive chemistry produce different 21st century Antarctic ozone projections, leading to differences in Southern Hemisphere westerly winds. This study adds another line of evidence as to why using interactive chemistry in a global climate model is important. It also acts as a cautionary tale for the next CMIP assessment, by showing that ozone forcing data sets must be produced in a way that is as consistent as possible with other CMIP forcings. Key Points: Interactive chemistry models project more 21st century Antarctic ozone than no‐chemistry models Ozone differences arise from inconsistent forcings used by models with/without interactive chemistry Larger ozone increases lead to smaller increases in Southern Hemisphere surface westerlies